2018
DOI: 10.1177/0170840618782278
|View full text |Cite
|
Sign up to set email alerts
|

Organizing the Environmental Governance of the Rare-Earth Industry: China’s passive revolution

Abstract: The rare-earth industry is of strategic importance for China and many 'clean' technologies worldwide. Yet the processes of mining, smelting and separating rare-earth ores are heavily polluting. Using a neo-Gramscian perspective in the context of organization studies, this article analyzes the dynamic interactions between government agencies, business and civil society in the development of the environmental governance of China's rare-earth industry over the past 30 years, with a particular focus on China's 'to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…We also extend IB and management studies of the conflict dynamics connected to governance problems (Kolk & Lenfant, 2010 to the context of state capitalism, where the entangled relationship between SOMNEs and the state, reliance on networks and cognitive institutions (Puffer & McCarthy, 2007) lead to active behind-the-scenes interaction between SOMNEs and governmental bodies. While we embrace contextuality, we suggest that our conceptual findings may be useful for understanding conflict escalation and outcomes in other settings with considerable state involvement in the economy and the absence of liberal market economy institutions in the local context, such as China 6 and Saudi-Arabia (Bo, Böhm, & Reynolds, 2018;Hui, 2017;Marquis & Qian, 2014;Paul et al 2018). In these settings corporations and the power elites of the state tend to be deeply intertwined in various ways (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…We also extend IB and management studies of the conflict dynamics connected to governance problems (Kolk & Lenfant, 2010 to the context of state capitalism, where the entangled relationship between SOMNEs and the state, reliance on networks and cognitive institutions (Puffer & McCarthy, 2007) lead to active behind-the-scenes interaction between SOMNEs and governmental bodies. While we embrace contextuality, we suggest that our conceptual findings may be useful for understanding conflict escalation and outcomes in other settings with considerable state involvement in the economy and the absence of liberal market economy institutions in the local context, such as China 6 and Saudi-Arabia (Bo, Böhm, & Reynolds, 2018;Hui, 2017;Marquis & Qian, 2014;Paul et al 2018). In these settings corporations and the power elites of the state tend to be deeply intertwined in various ways (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Despite their relevance for research on hegemony and resistance (e.g. Bo et al, 2019; Girei, 2016), social movements (e.g. Böhm et al, 2008; Spicer and Böhm, 2007), climate change (e.g.…”
Section: The Phenomenon Food Waste and The Phenomenon Dumpster Divingmentioning
confidence: 99%
“…First, this study introduces structural violence into neo-Gramscian analysis (e.g. Bo et al, 2019; Böhm et al, 2008; Levy and Egan, 2003; Levy and Newell, 2002) and shows how the structural violence perspective on the economic sphere facilitates a social justice-based, fundamental, critique of the hegemonic neoliberal social order.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research (e.g. Moog et al, 2015;Coleman, 2013;Himley, 2014;Li, 2016;Maher, 2018;Bo et al, 2018) has indicated that, despite their normative coherence, it seems only an ineffective and simulated governance -or, as Walters calls it, 'anti-politics' (2004, p. 33) -is generated when the dialogical and deliberative potential of those who defend public interests via enterprise strategies is undermined because of their managerial dependency on more operationally capable, and thus, more powerful corporations (see Moog et al, 2015;Lemke, 2007). Another, even more significant issue relates to the underestimation of the state's actual influence, because of PCSR's normative bias and alignment with an 'ideal future', in detriment of a historical assessment of the state's material organization and actual influence (Gond et al, 2011).…”
Section: (Re)encountering the Organized State: From Governance To Govmentioning
confidence: 99%
“…Their importance has led to a normative call for a ‘political CSR’ approach, arguing for an unequivocal political perspective of the corporation and the business conduct of its agents with multiple stakeholders (Mason & Simmons, 2014; Scherer & Palazzo, 2011; Wettstein, 2009). Yet, in the political CSR literature the role of the state has not been sufficiently understood (Bo, Böhm & Reynolds, 2018; Gond, Kang, & Moon, 2011; Knudsen & Moon, 2017), and hence there have been calls within OS for a renewed problematization of the state in CSR and governance regimes (Djelic & Etchanchu, 2015; Schrempf-Stirling, Palazzo, & Phillips, 2016; Whelan, 2012). Most of these calls have focused on highlighting the continued importance and relevance of the state in organizing business–society relations.…”
Section: Introductionmentioning
confidence: 99%